An international survey of imaging practices in radiotherapy. (October 2021) - Martin, C.J.; Kron, T.; Vassileva, J.; Wood, T.J.; Joyce, C.; Ung, N.M.; Small, W.; Gros, S.; Roussakis, Y.; Plazas, M.C.; Benali, A-H.; Djukelic, M.; et al.
Highlights: A survey of imaging in radiotherapy at 97 centres in 9 countries is reported. The majority of centres used imaging at every fraction. Facilities available for imaging during treatment declined with country HDI level. Centres used imaging protocols supplied by vendors with limited adjustment. Recording of patient doses from imaging was limited or non-existent. Abstract: Improvements in delivery of radiation dose to target tissues in radiotherapy have increased the need for better image quality and led to a higher frequency of imaging patients. Imaging for treatment planning extends to function and motion assessment and devices are incorporated into medical linear accelerators (linacs) so that regions of tissue can be imaged at time of treatment delivery to ensure dose distributions are delivered as accurately as possible. A survey of imaging in 97 radiotherapy centres in nine countries on six continents has been undertaken with an on-line questionnaire administered through the International Commission on Radiological Protection mentorship programme to provide a snapshot of imaging practices. Responses show that all centres use CT for planning treatments and many utilise additional information from magnetic resonance imaging and positron emission tomography scans. Most centres have kV cone beam CT attached to at least some linacs and use this for the majority of treatment fractions. The imaging options available declined with the human development index (HDI) of the country, and the frequency of imaging during treatment depended more on country than treatment site with countries having lower HDIs imaging less frequently. The country with the lowest HDI had few kV imaging facilities and relied on MV planar imaging intermittently during treatment. Imaging protocols supplied by vendors are used in most centres and under half adapt exposure conditions to individual patients. Recording of patient doses, a knowledge of which is important in optimisation of imaging protocols, was limited primarily to European countries.